Comparison of the effects of three different resistance training methods on muscle fatigue in healthy untrained men - Kadota, Masafumi; Nakamura, Masatoshi; Yoshida, Riku; Takeuchi, Kosuke (Frontiers in Sports and Active Living, 2024)
Introduction Traditional set (TS), paired-set (PS), and super-set (SS) are used as resistance training methods. However, the effects of these methods on muscle fatigue (muscle strength and training volume) are not clear. The purpose of this study was to compare the effects of TS, PS, and SS on the muscle fatigue of the hamstrings and quadriceps. Methods Thirteen healthy, untrained men performed three sets of leg curl and leg extension exercises. TS included three successive sets of the leg curl and leg extension exercises with a 60 s rest interval between sets and exercises. In the PS, leg curl exercises were performed alternatingly with the leg extension exercises with a 60 s rest interval between sets and exercises. In the SS, leg curl and leg extension exercises were performed alternatively with each set. During SS, a 60 s rest interval was set between sets but not between exercises. Muscle strength before and immediately after interventions, and training volume during the training, were measured using an isokinetic dynamometer machine. Time efficiency was calculated by dividing the total training volume by the time required for each intervention. Results and discussion The muscle strength of the hamstrings decreased in PS (p = 0.039) and SS (p = 0.001) but did not change in TS (p = 0.434). Muscle strength of the quadriceps decreased in all interventions (p < 0.05). In all interventions, the training volume of the hamstrings decreased in Set 2 (p < 0.05), and that of the quadriceps decreased in Set 3 (p < 0.05). The total training volume in PS was higher than TS (p < 0.01) and SS (p = 0.03). Time efficiency in SS was higher than TS (p < 0.01) and PS (p < 0.01). These results indicated that PS could be useful for individuals with sufficient time for resistance training because of greater training volume, while SS could be useful for those with limited time due to better time efficiency.